Photocatalytic seawater desalination: the effect of metal loading in the hybrid tio2 and the effect of wavelength - Afiq Hafizi, Azizi (2015)
Hybrid photocatalyst of Titanium Dioxide (TiO2) and biomass ash catalyst become an attractive alternative promoter for seawater desalination. The effect of metal loading in the seawater desalination via photocatalytic reaction at different wavelength light source was investigated. The hybrid catalyst with different weight ratio of TiO2, Oil palm fiber ash and metal loading either Nickel or Ferum was synthesized via wet impregnation. The catalysts were then characterized by using Scanning Electron Microscopy (SEM), Brunauer Emmett Teller (BET), X-ray Diffraction (XRD). The natural seawater were analysed for its pH, conductivity, turbidity, Biochemical Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) prior the experiment. Then the catalyst was tested with the natural seawater using photocatalytic reactor with the weight ratio of 1:400 catalyst and seawater. The experiment was conducted for two hours in a mercury light exposure with the wavelength of 365 nm and 420 nm respectively. The pH, conductivity, turbidity, BOD and COD of the final product were analysed. It is found that there was an increment of the seawater quality in term of salt concentration, COD and BOD. By using 365 nm wavelength light and nickel loading catalyst, the salt concentration, COD and BOD reduced up to 4%, 88%, and 68% respectively. Meanwhile, the reduction of COD and BOD were achieved at 95% and 97% when 420 nm wavelength light and ferum loading catalyst were used. At 420 nm wave length, the salt concentration was increasing due to the distillation. It because at 420 nm wavelength the water was heated up to 100 ◦C and causing the distillation to dominates the process. Nickel loading catalyst perform at best when 365 nm light was used, while ferum loading work great when 420 nm light was used. It is because the performance of the metal loading was due to the different characterization of the metal band gap in which the smaller the band gap, the bigger the wavelength. Nickel has bigger band gap than ferum. It can be concluded that the addition of the metal loading improve the performance of the catalyst due to the different band characterization of the metal loading and changes of wavelength can affect the performance of the catalyst.